2017
DOI: 10.1371/journal.pone.0184747
|View full text |Cite
|
Sign up to set email alerts
|

Risk of myeloid neoplasms after radiotherapy among older women with localized breast cancer: A population-based study

Abstract: BackgroundThere are inconsistent and limited data regarding the risk of myeloid neoplasms (MN) among breast cancer survivors who received radiotherapy (RT) in the absence of chemotherapy. Concern about subsequent MN might influence the decision to use adjuvant RT for women with localized disease. As patients with therapy-related MN have generally poor outcomes, the presumption of subsequent MN being therapy-related could affect treatment recommendations.MethodsWe used the Surveillance, Epidemiology, and End Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Rather, the investigators found that radiotherapy may add to risk of marrow neoplasms when combined with chemotherapy for the treatment of breast cancer. In accordance with this result, a recent SEER based study also did not show an increased risk of t-MN in older women treated with surgery followed by radiation when compared to those who did not receive radiation [30]. Though it must be noted that the median follow up in this study was short at 48 months.…”
Section: Epidemiology Of T-mds After Therapeutic Radiation Exposuresupporting
confidence: 88%
See 1 more Smart Citation
“…Rather, the investigators found that radiotherapy may add to risk of marrow neoplasms when combined with chemotherapy for the treatment of breast cancer. In accordance with this result, a recent SEER based study also did not show an increased risk of t-MN in older women treated with surgery followed by radiation when compared to those who did not receive radiation [30]. Though it must be noted that the median follow up in this study was short at 48 months.…”
Section: Epidemiology Of T-mds After Therapeutic Radiation Exposuresupporting
confidence: 88%
“…Earlier studies suggested an increased risk of leukemia in breast cancer patients treated with adjuvant radiation alone [27]. However, more recent studies suggest that radiation alone does not increase the risk of t-MN [28][29][30]. A recent analysis from the National Comprehensive Cancer Network (NCCN) Breast Cancer Outcomes Database suggests that radiation therapy alone does not significantly increase the risk of marrow neoplasms including MDS (HR=2.6; 95% CI: 0.57 to 11.9; P.21) in breast cancer patients [29].…”
Section: Epidemiology Of T-mds After Therapeutic Radiation Exposurementioning
confidence: 99%
“…for localized breast cancer) with subsequent development of t-MN is more controversial. (16,21,22) Patients with AD who develop a secondary leukemia typically develop AML rather than acute lymphoblastic leukemia (ALL). An increased incidence of AML has been reported across several AD types such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), polymyalgia rheumatica, ankylosing spondylitis, autoimmune hemolytic anemia, systemic vasculitides, pernicious anemia, multiple sclerosis (MS), and inflammatory bowel disease (IBD).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common malignancy in females, accounting for ~1/3 of all types of cancer ( 1 ). Despite advances in the detection and treatment of primary and metastatic cancers, and the application of surgery, radiotherapy, chemotherapy, immunotherapy and drug combinations, the mortality rate from cancer remains high, and side effects from the aforementioned combined treatments are severe ( 2 ). Therefore, identifying a more effective and less dangerous therapy for cancer is imperative.…”
Section: Introductionmentioning
confidence: 99%